Success Rate of Direct Hydroponic Cultivation Counseling and Training to Increase the Knowledge of Mothers in Sambirejo Village on Nutritional Fulfillment in Babies - Widya Yustika; Humairah Medina Liza Lubis; Nurcahaya Sinaga (UMSU, 2026)
Abstract: The success rate of direct extension and training in hydroponic cultivation can be measured by several indicators, including knowledge improvement, skill improvement, hydroponic cultivation implementation, and production success. Hands-on counseling and training on hydroponic cultivation is about the importance of providing information and training to farmers or individuals interested in starting hydroponic cultivation. With hydroponic cultivation and the harvest obtained can provide nutritional fulfillment to babies because they contain many nutrients that are very important given during the period of growth and early development of life. This study uses a purposive sampling technique, which is the deliberate selection of subjects based on suitability for the purpose of the research, namely mothers who are willing to participate in hydroponic cultivation counseling and training. Before the activity, respondents underwent a pre-test to measure initial knowledge. Counseling was delivered through a PowerPoint presentation on the types, needs, sources, and selection of nutrition in babies, followed by hydroponic cultivation training. After that, a post-test is carried out to assess the improvement in knowledge. The data is analyzed using the Dependent T Test test, or Wilcoxon test if the data distribution is abnormal. The average value of knowledge before direct counseling and training was 1.8, while knowledge after direct counseling and training was 2.7. The results showed an increase in the average knowledge of 0.9. In conclusion, there is a success rate of counseling and direct training in hydroponic cultivation to increase the knowledge of mothers in Sambirejo Village on the fulfillment of nutrition in babies